Functional reassignment of Cellvibrio vulgaris EpiA to cellobiose 2-epimerase and an evaluation of the biochemical functions of the 4-O-β-d-mannosyl-d-glucose phosphorylase-like protein, UnkA. Issue 6 (3rd June 2015) - Saburi, Wataru; Tanaka, Yuka; Muto, Hirohiko; Inoue, Sota; Odaka, Rei; Nishimoto, Mamoru; Kitaoka, Motomitsu; Mori, Haruhide
Abstract: The aerobic soil bacterium Cellvibrio vulgaris has a β-mannan-degradation gene cluster, including unkA, epiA, man5A, and aga27A. Among these genes, epiA has been assigned to encode an epimerase for converting d -mannose to d -glucose, even though the amino acid sequence of EpiA is similar to that of cellobiose 2-epimerases (CEs). UnkA, whose function currently remains unknown, shows a high sequence identity to 4- O -β-d -mannosyl-d -glucose phosphorylase. In this study, we have investigated CE activity of EpiA and the general characteristics of UnkA using recombinant proteins from Escherichia coli . Recombinant EpiA catalyzed the epimerization of the 2-OH group of sugar residue at the reducing end of cellobiose, lactose, and β-(1→4)-mannobiose in a similar manner to other CEs. Furthermore, the reaction efficiency of EpiA for β-(1→4)-mannobiose was 5.5 × 10 4 -fold higher than it was for d -mannose. Recombinant UnkA phosphorolyzed β-d -mannosyl-(1→4)-d -glucose and specifically utilized d -glucose as an acceptor in the reverse reaction, which indicated that UnkA is a typical 4- O -β-d -mannosyl-d -glucose phosphorylase. Graphical abstract: : Functional analysis of Cellvibrio vulgaris EpiA and UnkA proteins suggested that this bacterium degrades β-(1→4)-mannobiose through the epimerization and phosphorolysis.